Crystal structure of S -(4-methylbenzyl) piperidinedithiocarbamate - Rahima, Z. A.; Abdul Halim, Siti Nadiah; How, Fiona Ni Foong (International Union of Crystallography, 2015)
The title compound, C14H19NS2, crystallizes in the thione form with the presence of a C=S bond. The piperidine ring adopts a chair conformation. The dihedral angle between the essentially planar dithiocarbamate and p-tolyl fragments is 74.46 (10)deg.